PENDEKATAN PICTURE EXCHANGE COMMUNICATION SYSTEM (PECS) TERHADAPÂ KEMAMPUAN BICARA DAN KOMUNIKASI PROGRAM KEBUTUHAN KHUSUS PADA SISWA AUTIS DI SLB - DIAN ANGGRAINI, VIDYA (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   Speech and communication were one of the disorders experienced by autism children. One of the ways to help solving the problem was that the researcher used Picture Exchange Communication System approach toward speech and communication ability of special need program to autism students in SLB Autism Mutiara Hati Mojokerto. The purpose of this research was to prove whether there was influence of Picture Exchange Communication System (PECS) approach toward speech and communication ability of special need program to autism students. This research was implemented by using quantitative approach, pre-experimental arrangement, and one group pretest-posttest design. The sample used numbered 6 autism students in SLB Autism Mutiara Hati Mojokerto. The data collection was done by test and documentation techniques. After the data had been collected, it was then processed by statistic non parametric and then the data was analyzed by sign test formula. The research result indicated that there was enhancement of pretest average value i.e. 48,7 and posttest 70,2 while the result of data analysis indicated that Zh value was 2,05 and Z table 5% was 1,96 so the interpretation was Zh > Zt. It could be concluded that Ha was accepted it meant that there was influence of Picture Exchange Communication System (PECS) application toward speech and communication ability of special need program to autism students in SLB Mutiara Hati Mojokerto. Keywords: Picture Exchange Communication System approach, speech and communication ability